Role of reticuloendotheliosis virus envelope glycoprotein in superinfection interference. - Delwart, E L (1989)
Cells expressing specific proviruses are resistant to superinfection by viruses of the same subgroup. To investigate the role of the reticuloendotheliosis virus (REV) envelope glycoprotein (env-gp) in the establishment of resistance to superinfection, we constructed plasmids that express either the wild-type env-gp or an env-gp derivative that lacks part of the transmembrane (TM) protein. After transfection, transient expression of the wild-type env gene resulted in syncytium formation in a mammalian cell line permissive for virus replication, whereas synthesis of the TM-defective env-gp did not result in syncytium formation. Several stable cell lines expressing either the normal or TM-defective env-gp were isolated. Expression of the normal env-gp in the absence of expression of other viral genes induced resistance to infection by REV. Immunofluorescence analysis of cells expressing the TM-defective env derivative and an examination of the glycosylation pattern of this peptide indicated that it is not translocated to the cell surface but resides primarily in the rough endoplasmic reticulum. However, these cells were also resistant to REV infection. Thus, interaction between the env derivative and the cellular component that functions as a receptor for the virus can occur in the endoplasmic reticulum and renders the cell immune to superinfection.